Nearest interval-valued approximation of interval-valued fuzzy numbers - Ahmadian, Ali; Senu, Norazak; Salahshour, Soheil; Suleiman, Mohamed (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this paper, we proposed a new interval-valued approximation of interval-valued fuzzy numbers, which is the best one with respect to a certain measure of distance between interval-valued fuzzy numbers. Also, a set of criteria for interval-valued approximation operators is suggested.